Regulation and control method for photon spin-orbit coupling in organic alloy microcavity
By incorporating DCA into Pe, β-type Pe1-xDCAx organic alloys are prepared, and using them to regulate photon spin-orbit coupling in organic microcavities, the regulation problems in the prior art are solved, and the photophysical properties of microcavities are improved.
Patent Information
- Application Number
- CN202411563085.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The prior art is difficult to effectively regulate photon spin-orbit coupling in organic microcavities, limiting the development of nonlinear optics and photon systems.
By incorporating DCA into Pe, a β-type Pe1-xDCAx organic alloy was prepared, and used as a photoelectric material layer to regulate the doping amount of DCA, so as to achieve the regulation of photon spin orbit coupling in the organic alloy microcavity.
Effective regulation of photon spin orbit coupling in organic alloy microcavities is achieved, the photophysical properties of microcavities are improved, and a new microcavity is provided for studying the interaction between light and matter in organic alloy microcavities.
Smart Images

Figure CN119431100A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical microcavities, and in particular to a method for regulating photon spin-orbit coupling in an organic alloy microcavity. Background Art
[0002] Organic microcavities have low raw material costs and are easy to prepare with simple processes, which is conducive to the design and realization of artificially mediated microcavities and has strong applications in the field of nonlinear optics. TE-TM Spin-Orbit Coupling refers to the appearance of a k-dependent effective magnetic field caused by the transverse electric field-transverse magnetic field (TE-TM) splitting when the photon spin and orbit in the microcavity interact. The regulation of spin-orbit coupling in organic microcavities is the basis for the development of nonlinear optics and photonic systems.
[0003] Organic crystals have the advantages of being relatively easy to prepare and being in a metastable state at room temperature. The birefringence and anisotropy of organic micro-nano crystals play an important role in studying polarized light; the long-range order and long-range coherence caused by their spatial arrangement enable low-threshold lasers, valley excitation, and nonlinear topology. Organic alloys are single crystals with naturally excellent anisotropy and have broad application prospects in the field of microcavities. It is of great significance to develop high-performance organic alloys for microcavities and suitable spin-orbit coupling control methods. Summary of the invention
[0004] The purpose of the present invention is to provide a method for regulating photon spin-orbit coupling in an organic alloy microcavity to solve the problems existing in the above-mentioned prior art. The present invention obtains β-type Pe by doping DCA into Pe. 1-x DCA x Organic alloys are used to prepare organic microcavities, and the spin-orbit coupling in the organic alloy microcavities is regulated by regulating the doping amount of DCA.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention: a method for regulating photon spin-orbit coupling in an organic alloy microcavity, comprising the following steps:
[0007] β-type Pe 1-x DCA x The organic alloy is used as the photoelectric material layer to prepare an organic alloy microcavity;
[0008] By 1-x DCA x The regulation of x value in organic alloys can realize the regulation of photon spin-orbit coupling in organic alloy microcavities, where x≤20wt% (x represents DCA in Pe 1-xDCA x The mass proportion in the organic alloy is [mass of DCA / (mass of Pe+mass of DCA)]×100%).
[0009] Further, x is preferably 0.5 wt%, 1 wt%, 5 wt%, 10 wt% or 20 wt%.
[0010] Furthermore, the β-type Pe 1-x DCA x Organic alloys have a crystalline structure.
[0011] Furthermore, the β-type Pe 1-x DCA x The organic alloy is prepared by using perylene (Pe) and 9,10-dicyanoanthracene (DCA) as raw materials, using dichloromethane and anhydrous ethanol as solvents, and volatilizing the solvents.
[0012] Furthermore, the volume ratio of dichloromethane to anhydrous ethanol in the solvent is 1:1; and the mass / volume ratio of perylene to the solvent is 1 mg:1 mL.
[0013] Furthermore, the amount of 9,10-dicyananthracene used is 0-20wt% of the sum of the amounts of perylene and 9,10-dicyananthracene used, that is, in terms of mass ratio, (perylene+9,10-dicyananthracene):9,10-dicyananthracene=1:0-0.2.
[0014] Furthermore, the solvent development is carried out at room temperature.
[0015] β-Pe 1-x DCA x The synthesis steps of organic alloys are simple, the raw materials are easy to obtain, and the cost-effectiveness is high.
[0016] The second technical solution of the present invention is an organic alloy microcavity, the structure of which from top to bottom includes:
[0017] An upper silver film, a photoelectric material layer and a lower silver film;
[0018] The photoelectric material layer is β-type Pe 1-x DCA x Organic alloy.
[0019] Furthermore, the thickness of the upper silver film is 50 nm, and the reflectivity is 92.5%; the thickness of the lower silver film is 150 nm, and the reflectivity is 99.9%; and the thickness of the photoelectric material layer is 0.2-6 μm.
[0020] Furthermore, the thickness of the photoelectric material layer is preferably 1.7-4.9 μm.
[0021] Furthermore, the substrate is glass with a silicon dioxide component.
[0022] Technical solution three of the present invention: The method for preparing the above-mentioned organic alloy microcavity comprises the following steps:
[0023] A lower silver film is evaporated on the substrate, and a β-type Pe is grown on the surface of the lower silver film by evaporation of the solvent. 1-x DCA x The organic alloy is used as the photoelectric material layer, and an upper silver film is evaporated on the surface of the photoelectric material layer.
[0024] Furthermore, the evaporation rate of the lower silver film is The evaporation rate of the upper silver film is
[0025] Furthermore, the β-type Pe 1-x DCA x The organic alloy is obtained by using perylene and 9,10-dicyanoanthracene as raw materials and dichloromethane and anhydrous ethanol as solvents through solvent evaporation.
[0026] Furthermore, the specific operation of the solvent is: mixing perylene, 9,10-dicyanoanthracene and a solvent to obtain a mixed solution; dripping the mixed solution onto the surface of the lower silver film and volatilizing it naturally at room temperature.
[0027] Furthermore, the volume ratio of dichloromethane to anhydrous ethanol in the solvent is 1:1; the mass / volume ratio of perylene to solvent is 1 mg:1 mL; and the amount of 9,10-dicyananthracene is 0-20 wt % of the sum of the amounts of perylene and 9,10-dicyananthracene.
[0028] The present invention mixes perylene and 9,10-dicyanoanthracene in a solvent, and then adds different amounts of acceptor molecule DCA by volatilization at room temperature. During the volatilization process, a series of β-type Pe 1-x DCA xOrganic alloy crystals are prepared to regulate the photophysical properties of organic alloys, and the organic alloys are used to prepare optical microcavities. The spin-orbit coupling in the organic alloy microcavity is regulated by regulating the amount of DCA added. The present invention verifies the correctness of the synthesis of organic alloys by means of fluorescence spectroscopy, absorption spectroscopy, X-ray diffractometer, etc., and proves the correctness of the design of the organic alloy microcavity. Through the test of fluorescence spectrum, it can be found that the wavelength of the main peak of the luminescence spectrum is different when different DCA is added. For example, the main peak of 0.5wt% DCA (x=0.5wt%) is at 555nm, while the main peak of 5wt% DCA (x=5wt%) is at 605nm. In addition, after adding different amounts of DCA, the anisotropy of emission and absorption has changed significantly. At the same time, the energy splitting at a specific wavelength in the microcavity formed by this type of organic alloy has changed and is related to its anisotropy. The greater the anisotropy, the greater the intermolecular transition dipole moment, the greater the energy splitting, and the higher the conversion rate of circularly polarized light. The changes in its anisotropy indicate the nature of a strong transition dipole moment.
[0029] The present invention also designs different β-type Pe under the same DCA doping ratio. 1-x DCA x The spin-orbit coupling is divided into two cases: spin-orbit coupling occurs at the location where the first winding is generated and spin-orbit coupling occurs at the location where the second winding is generated. It is found that the circularly polarized light conversion rate of spin-orbit coupling occurring at the location where the first winding is generated is much higher than that of spin-orbit coupling occurring at the location where the second winding is generated, indicating that the electric field distribution is different in microcavities of different thicknesses, which affects the position of the anticrossing in the electric field and affects the spin-orbit coupling.
[0030] The β-type Pe prepared by the present invention 1-x DCA x Organic alloys have good kinetic stability and are relatively easy to prepare. At the same time, this type of organic alloy has birefringence characteristics, which provides the possibility for in-depth research on circularly polarized light. At the same time, through the absorption spectrum property test, it can be observed that the anisotropy of this type of organic alloy has a great change. It can be seen that by incorporating acceptor molecules (DCA) to form organic alloys, it is a very good and feasible solution to regulate the crystal anisotropy and intermolecular transition dipole moment in turn, and then regulate the degree of TE-TM spin-orbit coupling in the microcavity. At the same time, this type of organic alloy microcavity can be used in quantum information processing and photonic chip system applications. In summary, this type of organic alloy microcavity is a good optical microcavity and optoelectronic material.
[0031] There are some related technologies in the prior art about α-type Pe 1-x DCA x Organic alloys have been reported, but there is no report on β-type Pe 1-x DCA xThe β-type Pe 1-x DCA x Organic alloys have stable kinetic properties and are easier to prepare at room temperature than α-type. Due to their unique molecular spatial structure, they can be prepared by volatilization to produce thicker samples than α-type, thus showing different photophysical properties. 1-x DCA x The description of the design and application of organic alloy microcavities can provide a way of thinking for the development of other alloy microcavities, which can continuously expand the types and quantity of alloy microcavities and open up new horizons for the discovery of new organic material microcavities.
[0032] The present invention discloses the following technical effects:
[0033] The present invention prepares β-type Pe by adding different amounts of DCA into Pe through a volatilization method. 1-x DCA x Organic alloy, which can adjust the crystal color from yellow-green to orange-red. In addition, the organic alloy has the characteristics of birefringence. When used to prepare optical microcavities, TE-TM spin-orbit coupling and Rashba-Dresselhaus spin-orbit coupling can be observed in the microcavity, providing a new type of microcavity for studying the interaction between light and matter in organic alloy microcavities.
[0034] The present invention finds that the change in the degree of spin-orbit coupling is related to the change in anisotropy, and the β-type Pe 1-x DCA x The changes in the anisotropy of organic alloys are related to the amount of DCA doped. 1-x DCA x The regulation of the x value in organic alloys realizes the method of regulating the photon spin-orbit coupling in the organic alloy microcavity, provides the prerequisite for the regulation of the spin Hall effect, and has applicability in optical communications, cold atoms and quantum information processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 is the structural formula of perylene and 9,10-dicyanoanthracene, wherein a is perylene and b is 9,10-dicyanoanthracene;
[0037] Figure 2 β-type Pe1-x DCA x Schematic diagram of the typical molecular structure of organic alloys, where a represents the lattice structure of Pe; b and c represent two random situations where DCA replaces the position of Pe;
[0038] Figure 3 Pe prepared in Examples 1 to 6 1-x DCA x Fluorescence images of organic alloy products, where a is Example 6, and b to f are Examples 1 to 5 respectively;
[0039] Figure 4 Pe prepared in Examples 1 to 6 1-x DCA x XRD diffraction spectrum of organic alloy product;
[0040] Figure 5 This is the fluorescence image of the Pe organic single crystal product obtained in Comparative Example 1;
[0041] Figure 6 The XRD diffraction spectrum of the Pe organic single crystal product obtained in Comparative Example 1;
[0042] Figure 7 Pe prepared in Examples 1 to 6 1-x DCA x TEM images of organic alloy products, wherein a is Example 6, and b to f are Examples 1 to 5 respectively;
[0043] Figure 8 Pe prepared in Examples 1 to 6 1-x DCA x Absorption and emission spectra of organic alloy products;
[0044] Fig. 9 Pe prepared in Examples 1 to 6 1-x DCA x Anisotropy of absorption spectrum of organic alloy product, wherein a is Example 6, b to f are Examples 1 to 5 respectively;
[0045] Fig.10 Fluorescence photograph (a) and absorption and emission spectra (b) of raw material DCA;
[0046] Fig.11 The emission spectrum anisotropy (a) and absorption spectrum anisotropy (b) of raw material DCA;
[0047] Fig.12 Schematic diagram of the structure of the organic alloy microcavity;
[0048] Fig.13is the reflectivity of the upper layer and the lower layer of the organic alloy microcavity prepared in Application Example 1, wherein a is the upper layer and b is the lower layer;
[0049] Fig.14 Pe prepared in Application Example 1 1-x DCA x Reflection spectra of organic alloy microcavities with different DCA doping amounts in the organic alloy optoelectronic material layer, where a~f are Pe 1-x DCA x TE-TM splitting energy of organic alloy microcavities with different DCA doping amounts in the organic alloy optoelectronic material layer at 2.4 eV, g~l is Pe 1-x DCA x The Stokes parameter S3 of the organic alloy microcavity with different DCA doping amounts at the same energy; the black squares in m are the splitting values extracted at 2.4 eV in a~f; the blue and red dots in n are the left-handed (δ + ) and right-handed (δ + ) The degree of circular polarization;
[0050] Fig.15 Pe prepared in Application Examples 2 to 4 1-1wt% DCA 1wt% Reflection spectra of organic alloy microcavities with different thicknesses of organic alloy photoelectric material layers, where a~c are the TE-TM splitting energies of organic alloy microcavities with different thicknesses of photoelectric material layers at an energy of 2.5 eV, d~f are the Stokes parameters S3 of organic alloy microcavities with different thicknesses of photoelectric material layers at the same energy; the blue and red dots in g are the left-handed (δ + ) and right-handed (δ + ) The degree of circular polarization;
[0051] Fig.16 Schematic diagram of the process of dipole moment affecting photon spin-orbit coupling in a microcavity;
[0052] Fig.17 : Reflection spectra of the organic alloy microcavity with the β-type Pe organic single crystal of Example 6 as the photoelectric material layer and the organic alloy microcavity with the Pe organic single crystal of Comparative Example 1 as the photoelectric material layer, wherein a and b are the control ranges of the thickness of the photoelectric material layer of the microcavity with the β-type Pe organic single crystal of Example 6 as the photoelectric material layer, and c and d are the control ranges of the thickness of the photoelectric material layer of the microcavity with the Pe organic single crystal of Comparative Example 1 as the photoelectric material layer. DETAILED DESCRIPTION
[0053] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0054] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0055] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0056] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0057] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0058] The "%" involved in the specific embodiments of the present invention represents mass percentage.
[0059] The raw materials and reagents used in the specific embodiments of the present invention are all commercially available products.
[0060] Figure 1 is the structural formula of perylene and 9,10-dicyanoanthracene used in a specific embodiment of the present invention, wherein a is perylene and b is 9,10-dicyanoanthracene.
[0061] Example 1
[0062] β-Pe 1-x DCA x Preparation of organic alloys:
[0063] Take 2 mg of perylene powder and 0.01 mg of 9,10-dicyanoanthracene, put them into a 5 mL centrifuge tube, then add 1 mL of dichloromethane and 1 mL of anhydrous ethanol to obtain a mixed solution; use a pipette to draw 150 μL of the mixed solution and drop it on the cover glass, and evaporate it naturally at room temperature of 25 ° C to obtain β-type Pe 1-x DCA x The organic alloy crystal, wherein the amount of 9,10-dicyanoanthracene is 0.5 wt % of the sum of the amounts of perylene and 9,10-dicyanoanthracene (ie, x is 0.5 wt %).
[0064] Example 2
[0065] Compared with Example 1, the only difference is that the amount of 9,10-dicyanoanthracene is 0.02 mg, that is, the amount of 9,10-dicyanoanthracene is 1 wt% of the sum of the amounts of perylene and 9,10-dicyanoanthracene. The prepared β-type Pe 1-x DCA x The x in the organic alloy crystal is 1 wt %.
[0066] Example 3
[0067] Compared with Example 1, the only difference is that the amount of 9,10-dicyanoanthracene is 0.105 mg, that is, the amount of 9,10-dicyanoanthracene is 5wt% of the sum of the amounts of perylene and 9,10-dicyanoanthracene. 1-x DCA x The x in the organic alloy crystal is 5 wt %.
[0068] Example 4
[0069] Compared with Example 1, the only difference is that the amount of 9,10-dicyanoanthracene is 0.22 mg, that is, the amount of 9,10-dicyanoanthracene is 10 wt % of the sum of the amounts of perylene and 9,10-dicyanoanthracene. 1-x DCA x The x in the organic alloy crystal is 10 wt %.
[0070] Example 5
[0071] Compared with Example 1, the only difference is that the amount of 9,10-dicyanoanthracene is 0.5 mg, that is, the amount of 9,10-dicyanoanthracene is 20wt% of the sum of the amounts of perylene and 9,10-dicyanoanthracene. 1-x DCA x The x in the organic alloy crystal is 20 wt %.
[0072] Example 6
[0073] Compared with Example 1, the only difference is that the amount of 9,10-dicyanoanthracene used is 0, and the obtained product is β-type Pe organic single crystal.
[0074] Comparative Example 1
[0075] Take 2 mg of perylene and put it into a 10 mL centrifuge tube, then add 4 mL of dichloromethane and 4 mL of anhydrous ethanol to obtain a mixed solution; use a pipette to draw 150 μL of the above mixed solution and drop it on the cover glass, and evaporate it naturally at room temperature of 25°C to obtain Pe organic single crystals.
[0076] Application Example 1
[0077] Preparation of organic alloy microcavities:
[0078] A glass sheet with a silicon dioxide component was used as a substrate. A 150 nm thick silver film was evaporated at a deposition rate of 10000 to form a dense reflective layer with a reflectivity of about 99.9% as the lower layer; Pe in Examples 1 to 6 were prepared on the surface of the lower silver film. 1-x DCA x The organic alloy is used as the photoelectric material layer (the specific operation is to drop the mixed solution prepared in Examples 1 to 6 on the surface of the lower silver film with a dropper, and volatilize it naturally at room temperature of 25°C to obtain a 3.2 μm thick organic alloy photoelectric material layer); A 50nm thick silver film was evaporated at a deposition rate of 1.500 nm to form a reflective layer with a reflectivity of about 92.5% as the upper layer, and organic alloy microcavities with different DCA doping amounts in the photoelectric material layer were obtained. The structural schematic diagram of the prepared organic alloy microcavity is shown in FIG. Fig.12 shown.
[0079] Application Example 2
[0080] Compared with Application Example 1, the only difference is that the photoelectric material layer is Pe in Example 2. 1-1wt% DCA 1wt% The organic alloy is added by controlling the amount of the mixed solution added so that the thickness of the photoelectric material layer is 1.7 μm.
[0081] Application Example 3
[0082] Compared with Application Example 1, the only difference is that the photoelectric material layer is Pe in Example 2. 1-1wt% DCA 1wt% The organic alloy is added by controlling the amount of the mixed solution added so that the thickness of the photoelectric material layer is 3.8 μm.
[0083] Application Example 4
[0084] Compared with Application Example 1, the only difference is that the photoelectric material layer is Pe in Example 2. 1-1wt% DCA 1wt%Organic alloy, by controlling the amount of mixed solution added, the thickness of the photoelectric material layer is 4.9μm
[0085] Test example
[0086] Figure 2 Pe and β-type Pe 1-x DCA x Schematic diagram of the typical molecular structure of organic alloys, where a represents the lattice structure of Pe; b and c represent two random situations where DCA replaces the Pe position, respectively.
[0087] Figure 3 Pe prepared in Examples 1 to 6 1-x DCA x Fluorescence graphs of organic alloy products, where a is Example 6, and b to f are Examples 1 to 5, respectively. It can be seen from a and b to f that the fluorescence color of the product gradually changes from yellow-green to orange-red when the amount of DCA incorporated (i.e., the value of x) gradually increases, and the product is a rhombus (rhombus is generally the shape of β-type Pe), proving that under the condition that the concentration of perylene is 1 mg / mL, the solvent evaporates and the crystals tend to grow towards the β-type. Figure 4 Pe prepared in Examples 1 to 6 1-x DCA x The XRD diffraction spectrum of the organic alloy product (where 0.5%, 1%, 5%, 10%, and 20% all represent the value of x, Pe represents x is 0, and powder represents the XRD diffraction spectrum of the theoretically simulated β-type Pe organic single crystal) is obtained by Figure 4 It can be seen that the Pe obtained by adding different amounts of DCA in Examples 1 to 6 1-x DCA x The diffraction peak positions of the crystals are consistent, which shows that the different amounts of DCA doped do not change the lattice structure of the alloy, and the product can be determined to be an alloy. Moreover, the diffraction peak positions of Examples 1 to 6 are consistent with the diffraction peaks of the theoretically simulated β-type Pe organic single crystals, further proving that the Pe prepared in Examples 1 to 6 1-x DCA x The organic alloy product is indeed β-type Pe 1-x DCA x . Figure 5 The fluorescence image of the Pe organic single crystal product obtained in Comparative Example 1 is Figure 5 It can be seen that the product of Comparative Example 1 is a square (a square is generally the shape of α-type Pe), which proves that under the condition that the concentration of perylene is 0.25 mg / mL, the solvent evaporates and the crystal tends to grow toward the α-type. Figure 6 is the XRD diffraction spectrum of the Pe organic single crystal product prepared in Comparative Example 1 (where 0 represents the Pe organic single crystal prepared in Comparative Example 1, and powder represents the XRD diffraction spectrum of the α-type Pe organic single crystal simulated in theory), Figure 6It can be seen that the diffraction peak position of Comparative Example 1 is basically consistent with the diffraction peak of the theoretically simulated α-type Pe organic single crystal, but there is an additional peak at 9°, which further proves that the solvent evaporation crystals of Comparative Example 1 tend to grow towards the α-type when the concentration of perylene is 0.25 mg / mL, but the α-type crystals may not be pure during the growth process and may be doped with trace amounts of β-type crystals.
[0088] Figure 7 Pe prepared in Examples 1 to 6 1-x DCA x TEM images of organic alloy products, wherein a is Example 6, b to f are Examples 1 to 5 respectively, Figure 7 It can be seen that the two-dimensional microsheets with tilt angles of Examples 1 to 6 remain almost unchanged, which further illustrates the single crystal composition of the alloy, that is, the products are all pure β-type.
[0089] Figure 8 Pe prepared in Examples 1 to 6 1-x DCA x The absorption and emission spectra of the organic alloy product (where 0, 0.5%, 1%, 5%, 10%, and 20% all represent the value of x) are given by Figure 8 It can be seen that with the increase of DCA incorporation amount, the main peak of the emission spectrum has a large red shift (>50nm), reflecting the nature of the intramolecular transition dipole moment.
[0090] Fig. 9 Pe prepared in Examples 1 to 6 1-x DCA x The anisotropy of the absorption spectrum of the organic alloy product (tested with visible white light), wherein a is Example 6, b to f are Examples 1 to 5 respectively, Fig. 9 It can be seen that the anisotropy of crystal absorption is different when different amounts of DCA are doped, indicating that the different amounts of DCA doped have a great influence on the anisotropy of crystal absorption, where the polarization degrees when x is 0%, 0.5%, 1%, 5%, 10%, and 20% are 0.30, 0.32, 0.37, 0.29, 0.31, and 0.29, respectively.
[0091] Fig.10 The fluorescence photo (a) and absorption and emission spectra (b) of the raw material DCA are shown in Figure 2. Fig.10 It can be seen that DCA emits green light with an absorption peak at 450nm and PL at 540nm.
[0092] Fig.11 is the emission spectrum anisotropy and absorption spectrum anisotropy of raw material DCA, where a is the emission spectrum anisotropy and b is the absorption spectrum anisotropy. Fig.11It can be seen that the polarization magnitude of the emission spectrum is P=0.51, and the polarization magnitude of the absorption spectrum is p=0.40.
[0093] Fig.13 is the reflectivity of the upper and lower layers of the organic alloy microcavity prepared in Application Example 1, where a is the upper layer, b is the lower layer, and Fig.13 It can be seen that the reflectivity of the upper silver film is about 0.925, or about 92.5%, and the reflectivity of the lower silver film is about 0.999, or 99.9%, forming a perfect FP microcavity.
[0094] The microcavity was tested by using a self-built angle-resolved optical path. The anti-crossing point was adjusted to the same energy (wavelength). The reflection spectrum data and the corresponding polarization data were tested and the Stokes parameters were calculated. The results are as follows: Fig.14 shown.
[0095] Fig.14 Pe prepared in Application Example 1 1-x DCA x Reflection spectra of organic alloy microcavities with different DCA doping amounts in the organic alloy optoelectronic material layer, where a~f are Pe 1-x DCA x TE-TM splitting energy of organic alloy microcavities with different DCA doping amounts at 2.4 eV (a~f represent x as 0, 0.5wt%, 1wt%, 5wt%, 10wt% and 20wt%, respectively), g~l represent PeDCA x Stokes parameters S3 of organic alloy microcavities with different DCA doping amounts in the organic alloy photoelectric material layer at the same energy (g~l represent x as 0, 0.5wt%, 1wt%, 5wt%, 10wt% and 20wt%, respectively); the black squares in m are the splitting values extracted at 2.4eV in a~f, respectively, and the blue and red dots in n are the left-handed (δ + , blue) and right-handed (δ + , red) circular polarization degree. Fig.14 It can be seen that with the increase of Pe 1- x DCA x With the increase of DCA doping amount (i.e., the value of x) in organic alloy, the TE-TM splitting energy is different at the same energy, and the Stokes parameter S3 component changes with the change trend of splitting energy, indicating that the conversion rate of circularly polarized light is different, indicating that the total dipole moment of the molecule after DCA doping affects the molecular anisotropy, and then affects the change of its splitting energy and circularly polarized light conversion rate (i.e., the dipole moment affects the photon spin-orbit coupling in the microcavity, Fig.16 (Schematic diagram of the process of dipole moment affecting photon spin-orbit coupling in a microcavity).
[0096] Fig.15 Pe prepared in Application Examples 2 to 4 1-1wt% DCA 1wt% Reflection spectra of organic alloy microcavities with different thicknesses of organic alloy photoelectric material layers, where a~c are the TE-TM splitting energies of organic alloy microcavities with different thicknesses of photoelectric material layers at an energy of 2.5 eV (a~c represent application examples 2~4, respectively), d~f are the Stokes parameters S3 of organic alloy microcavities with different thicknesses of photoelectric material layers at the same energy (d~f represent application examples 2~4, respectively); the blue and red dots in g are the left-handed (δ + , blue) and right-handed (δ + , red) circular polarization degree. Fig.15 It can be seen that spin-orbit coupling occurs at the first winding in Application Examples 2 and 3, and spin-orbit coupling occurs at the second winding in Application Example 4. The circular polarization conversion rate of spin-orbit coupling at the first winding is much higher than that of spin-orbit coupling at the second winding. That is, the winding number affects the photon spin-orbit coupling in the microcavity.
[0097] Fig.17 The reflection spectra are of an organic alloy microcavity with a β-type Pe organic single crystal as the photoelectric material layer of Example 6 and an organic alloy microcavity with a Pe organic single crystal as the photoelectric material layer of Comparative Example 1 (the preparation method of the microcavity is the same as that of Application Example 1, and microcavities with different photoelectric material layer thicknesses are obtained by controlling the amount of mixed solution added), wherein a and b show the control range of the photoelectric material layer thickness of the microcavity with a β-type Pe organic single crystal as the photoelectric material layer of Example 6, and c and d show the control range of the photoelectric material layer thickness of the microcavity with a Pe organic single crystal as the photoelectric material layer of Comparative Example 1. Fig.17 It can be seen that within the same energy range of 2.6 to 2.4 eV, the mode number of the microcavity with the β-type Pe organic single crystal as the optoelectronic material layer in Example 6 can be adjusted from one group to three groups, while the microcavity with the Pe organic single crystal as the optoelectronic material layer in Comparative Example 1 can only be adjusted to about one group (in an optical microcavity, the number of optical modes can be used to preliminarily represent the thickness of the microcavity: the optoelectronic material layer of the microcavity with a large number of cavity modes is relatively thick, and the optoelectronic material layer of the microcavity with a small number of cavity modes is relatively thin. The thicknesses of the optoelectronic material layers of the microcavities in a, b, c, and d are 1.7 μm, 4.9 μm, 1.1 μm, and 1.6 μm, respectively).
[0098] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for regulating photon spin-orbit coupling in an organic alloy microcavity, characterized in that the steps include: β-type Pe 1-x DCA x The organic alloy is used as the photoelectric material layer to prepare an organic alloy microcavity; By 1-x DCA x The regulation of the value of x in the organic alloy realizes the regulation of the photon spin-orbit coupling in the organic alloy microcavity, wherein x≤20wt%.
2. The control method according to claim 1, characterized in that: The β-type Pe 1-x DCA x The organic alloy is prepared by using perylene and 9,10-dicyanoanthracene as raw materials, using dichloromethane and anhydrous ethanol as solvents, and volatilizing the solvents.
3. The control method according to claim 2, characterized in that: The volume ratio of dichloromethane to anhydrous ethanol in the solvent is 1:1; the mass / volume ratio of perylene to the solvent is 1 mg:1 mL.
4. The control method according to claim 2, characterized in that: The solvent evaporation is carried out at room temperature.
5. An organic alloy microcavity, characterized in that: The structure from top to bottom includes: An upper silver film, a photoelectric material layer and a lower silver film; The photoelectric material layer is β-type Pe 1-x DCA x Organic alloy, wherein x≤20wt%.
6. The organic alloy microcavity according to claim 5, characterized in that: The thickness of the upper silver film is 50nm, and the reflectivity is 92.5%; the thickness of the lower silver film is 150nm, and the reflectivity is 99.9%; the thickness of the photoelectric material layer is 0.2-6μm.
7. The method for preparing an organic alloy microcavity according to any one of claims 5 to 6, characterized in that the steps include: A lower silver film is evaporated on the substrate, and a β-type Pe is grown on the surface of the lower silver film by evaporation of the solvent. 1-x DCA x The organic alloy is used as the photoelectric material layer, and an upper silver film is evaporated on the surface of the photoelectric material layer.
8. The preparation method according to claim 7, characterized in that: The evaporation rate of the lower silver film is The evaporation rate of the upper silver film is
Citation Information
Patent Citations
Organic microcavity photodetectors with narrow and tunable spectral response
CN109791986A
Method for effectively regulating and controlling length of micro cavity
CN109936045A
Organic single crystal micro-strip capable of being used for organic electric pumping laser, and preparation method and application thereof
CN111647949A
Organic photoelectric detector based on optical microcavity effect and preparation method thereof
CN111952460A
Anti-stilbene skeleton molecule, synthetic method and application thereof, and organic microcavity exciton polariton light-emitting diode
CN115124503A